Development Of Teaching Materials In Mathematics Lessons In Semester Ii In Class IV Students Of Elementary School - Lizah, Rifaam; Asari, Slamet; Alfiansyah, Iqnatia (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This study aims to develop teaching materials in mathematics lessons for fourth grade elementary school students. The method in this study uses a 4D Thiagarajan development model consisting of 4 stages, namely define, design, develop, disseminate. Meanwhile, the researchers only reached the development stage. The subjects of this study were fourth grade students of UPT SDN 302 Gresik and 2 material expert validators namely elementary school fourth grade teachers and 2 teaching material design expert validators namely lecturers of FKIP Muhammadiyah University of Gresik. The data collection method used is validation and student response questionnaires. Based on the result of data analysis from validation and trial result, it was found that the development of mathematics teaching materials produced quality teaching materials, namely a) mathematics teaching materials were categorized as valid on material expert validation (96,87%) and expert validation of teaching material design (94, 16%) ; b) mathematics teacing materials are categorized as effective with the percentage of student response questionnaire score of 90,4%.